Slope Stability Analysis of High-Plasticity Overconsolidated Clay Using PLAXIS LE - Burhan Priyambodo; Sri Prabandiyani Retno Wardani; Kresno Wikan Sadono (Universitas Medan Area, 2026)
Slope instability in high-plasticity overconsolidated clay presents a significant challenge for infrastructure development due to the progressive reduction of soil shear strength caused by weathering and environmental changes. This study aims to evaluate the stability of a landslide slope located in Watujagir, Purworejo Regency, Central Java Province, Indonesia, using PLAXIS LE based on fully softened and residual shear strength parameters. Surface soil samples were collected from the landslide area and tested to determine the Atterberg limits. The liquid limit values were subsequently correlated with fully softened and residual friction angles using the empirical relationships proposed by Stark and Hussain. The slope geometry was reconstructed from field measurements and analyzed using the Limit Equilibrium Method implemented in PLAXIS LE. The laboratory results indicated liquid limit values ranging from 121.15% to 130.58%, representing highly plastic overconsolidated clay. The analysis produced a factor of safety of 0.990, indicating that the existing slope is in a critical unstable condition. The calculated failure mechanism corresponded to approximately 76% residual shear strength and 24% fully softened shear strength mobilization. These findings demonstrate that long-term shear strength degradation plays a dominant role in slope failure and should be incorporated into stability assessments of highly plastic overconsolidated clay slopes.